The Influence of Pharmaceutical Companies Marketing Activities on Physicians’ Prescribing: Literature Review - Putri, Felicita Eka; Satibi, Satibi; Syahlani, Suci Paramitasari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Pharmaceutical companies through marketing strategies introduce the products to the user. Physicians are the target of prescription drug marketing. For a long time, pharmaceutical companies have done many marketing activities. They are spend a big portion for the marketing activities. The aims of that activities, to influence physicians’ prescribing.Objectives: This article aimed to examine the influence of marketing activities from pharmaceutical companies on physicians’ prescribing in various countries.Methods: Scopus is used as a database to collect articles with keywords named “pharmaceutical marketing” and prescribing. Inclusion criteria are original articles, published in 2018-2023, in English, open access. In the end, eight articles were reviewed in this study.Results: The result of this study shows pharmaceutical companies apply a marketing mix strategy to promote their product. This strategy consists of four elements product, price, place, and promotion. All of the element influences physicians’ prescribing, generally. Promotion startegies such as medical representative visits and gifts are the most influential strategies for physicians’ prescribing. The influence can’t be generalized because it also depends on the socioeconomic state of the country, culture, work location or environment, practice experience,geography, and ethical issues.Conclusion: Promotion strategy is the most influential for prescribing than product, place, and price but the influence based oh the physicians’ characteristics. So, pharmaceuitcal compines must indentify their user to decide a appropriate strategy.